Continuous review inventory model with delay in payments - El-Kassar, A. N. (2003)
In this paper, we examine the continuous review inventory model under permissible delays in payments. That is, a retailer has the option of either paying for the goods immediately upon the receipt of the order or delay the payment till the next replenishment order, where interest will be charged over the delay period. Expected demand will be assumed constant over time, and the order lead-time is considered random. The objective is to find the optimal ordering quantity and reorder level that will maximize the vendor's total expected profit per unit time when payments are delayed.